Making ends meet in refugee camps: food distribution cycles, consumption and undernutrition - Aubery, F.; Buisson, Marie-Charlotte (Elsevier, 2024)
Years after the initial settlement, food aid remains an essential component of humanitarian assistance for protracted refugees in managed camps. From data collected among refugee households in three camps in southern Chad and an exogenous variation of time between the latest food distribution and households’ interviews, we draw the time path of household’s consumption. Consistent with the literature on intertemporal choices in high-income countries, refugee households experience an average decline of 1.1 to 1.5 percent per day in their daily caloric intake between distributions. The short-term nutritional status of children under five also responds to the distance from food aid distribution and confirms the existence of food distribution cycles. Our results suggest that households don’t smooth consumption during the interval of time between two distributions, and face regular and frequent cycles of food shortage resulting in detrimental consequences on children’s health.